PROSPECTS OF EARLY MATURING COTTON AND HEAT TOLERANT POTATO HYBRIDS FOR DIVERSIFICATION OF COTTON-WHEAT SYSTEM IN NORTH-WEST INDO-GANGETIC PLAINS - Singh, Devendra; Kumar, D; Sharma, S K; Pandey, R.; Singh, B. P.; Kumar, Vipin (Potato Journal, 2013)
Field experiments were conducted to test the suitability and adaptability of cotton and wheat genotypes for cotton-wheat system at PDCSR, Modipuram and identification of early sown, short duration potato genotypes at CPRI Campus, Modipuram. Fifteen cotton genotypes were grown during kharif 2004. After harvesting of cotton, six wheat genotypes were sown as sub plots on 20th November (normal sowing) and mid December (late sowing). In addition at CPRI campus, Modipuram five genotypes of potato were tested for early planting conditions (midSeptember) in RBD. Observations were recorded on days to harvestable maturity and yield of cotton, potato and wheat genotypes. Early maturing cotton genotypes (viz., Ankur 651 and CNH-36) harvested in mid–September produced a seed cotton yield of 1.8 t/ha. The wheat yield ranged from 5.07 to 5.48 t/ha depending upon its sowing time after cotton. The potato genotype HT/92-621 produced a good tuber yield of 1.42 to 1.98 t/ha in 60-75 DAS under early planting. The early maturing cotton genotypes and heat tolerant potato hybrids can provide opportunities for the diversification of cotton-wheat system by inclusion of potato in north-west Indo-gangetic plains and needs to be further tested in the system mode.